Evolution of a honeycomb network of precipitates in a hot-rolled commercial Mg-Y-Nd-Zr alloy - Choudhuri, D.; Meher, S.; Nag, S.; Dendge, N.; Hwang, J. Y.; Banerjee, R. (TAYLOR & FRANCIS LTD, 2013)
Coupled processes of dynamic recovery and precipitation, occurring during hot-rolling and subsequent aging, lead to the formation of a unique honeycomb network of precipitates in commercial Mg-Y-Nd-Zr or WE43 alloy. The honeycomb network is developed on the (0001)(Mg) basal planes and consisted of fine Nd-rich (1) platelets lying on all three planes presumably decorating recovery-generated dislocation subcell boundaries. Three variants of (1) platelets are connected by Y-rich precipitates at the nodes of the hexagonal honeycomb network.
Keywords: DYNAMIC PRECIPITATION; PHASES